Phonological variation in Akokoid (2013)
This paper examines the process of language change occasioned by different phonological processes in the nine speech forms which scholars have given different names, such as Northern Akoko Cluster (Hoffman 1974), Akokoid (Akinkugbe 1978), Amgbe (Capo 1989), Arigidi – Amgbe (Akinyemi 2002) and Arigidi- Owon (Fadoro 2008b). These nine speech forms are Arigidi, Erushu, Afa, Oge, Aje (Ese), Udo, Oyin, Igashi and Uro all spoken in the present Akoko North-West Local Government with its headquarters in Oke-Agbe, Ondo State of Nigeria. Through the direct method of data elicitation, the Ibadan 400 wordlist was used to obtain data from 30 informants. Selection of informants was guided by the acronym (NORMs) (Non-mobile, Old, Rural, Males). The major finding of this research is the fact that the speech forms in question have undergone systematic changes over time. These changes have occasioned phonological variation within the group. Arigidi (which is made up of Arigidi and Erushu) has twenty phonemic consonants, whereas Owon (which comprises Afa, Oge, Aje, Udo, Oyin, Igashi and Uro) has twenty-two. This difference in the number of consonant phonemes coupled with different phonological processes, such as nasalisation, palatalisation, spirantisation, simplification of complex segments, vowel raising, changes in tonal pattern, etc have resulted in phonological variation across the speech forms. This paper is not only a state of the art report on language change motivated by phonological variation, it examines how phonological variation is produced by mechanical systematic sound changes, affecting the original sounds of the language and how these sound changes affect the language of different sectors of the speech community in different ways, thus producing variation where once was homogeneity